Metabolic syndrome with mortality and major adverse cardiovascular events in an elderly population - Kumar Karn, Shailendra; Zhao, Fang; Xu, Yawei; Zhang, Yi; Zeng, Chunlai; Shaikh, Imran Ibrahim; Singh, Shekhar; Feng, Yuling (Frontiers in Endocrinology, 2025)
BackgroundCardiovascular disease (CVD) remains a leading cause of morbidity and mortality globally, with metabolic syndrome (MS) being a significant contributor to major adverse cardiovascular events (MACE). While the relationship between MS and CVD is well established, limited studies have focused on elderly populations, particularly in the context of long-term cardiovascular outcomes. This study aims to fill this gap by investigating the impact of MS and its components on MACE in an elderly population.MethodsWe conducted a prospective cohort study involving 3,352 elderly residents from the Northern Shanghai Study (NSS), followed for an average of 5.6 years. MS was defined based on modified NCEP ATP III criteria. The primary outcome was MACE, including non-fatal myocardial infarction (MI), non-fatal stroke, cardiovascular death, and all-cause mortality. Kaplan-Meier survival analysis and multivariate logistic regression were used to examine the association between MS and MACE.ResultsMS was present in 44.2% of the cohort. Participants with MS had a significantly higher incidence of MACE compared to those without MS (12.69% vs. 9.30%, p=0.02). MS was confirmed as an independent risk factor for MACE (HR 1.471, 95% CI 1.195–1.181, p=0.001). Among the individual components of MS, the combination of central obesity, hypertension, and hyperglycemia (ABD+BP+GLU) showed the strongest predictive value for MACE (HR 3.001, 95% CI 1.640–5.492, p<0.001).ConclusionsMS is an independent predictor of MACE in elderly populations, with central obesity, hypertension, and hyperglycemia being the most critical risk factors. These findings underscore the importance of early identification and management of MS to reduce cardiovascular risk and improve long-term outcomes in elderly individuals.